Achieving the Criteria of a SAMARA Family in the Household - Alfarisi, Achmad Hasan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Achieving the criteria of a SAMARA family (Sakinah, Mawaddah, Rahmah) in a household involves cultivating an environment of peace, love, and compassion within the family. Islamic Sharia provides a divine framework for family life, emphasizing the importance of faith, mutual respect, and fulfilling the duties and rights of each family member. The pursuit of a SAMARA family begins with mutual understanding, trust, and support between husband and wife, underpinned by a shared commitment to religious values and the application of these principles in daily life. This study explores the essential components of a SAMARA family, which include emotional harmony (Sakinah), love and affection (Mawaddah), and compassion (Rahmah), all of which contribute to a balanced and sustainable marital relationship. By adhering to these principles, families can overcome challenges and create a nurturing environment that fosters both individual and collective well-being. The goal of this study is to outline the steps and strategies necessary to build a SAMARA family, ensuring the stability and prosperity of the household, in line with Islamic teachings.